The Encyclopedia of sea warfare : from the first ironclads to the present day - Parsons, Iain (New York : Crowell, 1975)
"The encyclopedia of sea warfare covers the dramatic events of naval history during the period of its most rapid and exciting developments ... The book gives a fascinating insight into the strategic planning, the tactical thinking and the historical implications of the battles and wars fought at sea from the age of the ironclads to the nuclear age"--Jacket.
Hampton Roads to Tsushima -- The first clash of ironclads -- New power at sea -- Fleets in conflict -- World War I -- 'Commence hostilities' -- Failure in the Med -- The fight in the far seas -- Skirmishes in the North Sea -- Jutland--the clash of the fleets -- Sea power ends the war -- World War II-European waters -- Europe's navies prepare for war -- A sea war in earnest -- Battle begins in the Atlantic -- Fluctuating fortunes in the Med -- Action in Arctic waters -- Decision in the Atlantic -- Victory in the Med -- The end of German naval power -- World War II-the Pacific -- Strike and counterstrike--Pearl Harbor to Midway -- On to the offensive--Guadalcanal to the Admiralties -- The big leap--the Gilberts to Guam -- Return engagement--Philippines and Leyte Gulf -- The drive for victory--Rangoon to Hiroshima -- The Nuclear Age -- The world-wide role of sea power -- Korea and Vietnam--sea power in action -- Technology takes over at sea -- Carriers supreme -- Submarine power -- The impact of technology -- Sea power--the critical balance.
Includes index.
Also issued online.
Keywords: Geschichte 1863.; Naval art and science -- History; Naval history; Naval art and science; Naval history; Marine; Seekrieg; Encyclopedia; encyclopedias; Encyclopedias; History